Innovation and firm creation strategies in the emerging biotechnology industries - Said, Mohd Fuaad; Adham, Khairul Akmaliah; Abdullah, Nur Atiqah; Sarkam, Saida Farhanah; Quoquab, Farzana; Hanninen, Seppo (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
Innovation and firm creation are enablers of industry development, especially in industries that are technology-intensive. In the contexts of an emerging industry, industry development supports the transformation of an emerging economy into a developed one. Therefore, by understanding innovation and firm creation strategies and the variables that influence them entrepreneur-managers will be able to design strategies for the development of their firms, and policy makers will be able to institute a conducive environment which support rapid growth of the industry. This study examines the strategies for innovation and firm creation adopted by 92 companies in the emerging Malaysian biotechnology sector. The objective is to gain an understanding of the variables that influence their innovation and firm creation strategies. To achieve this objective, content analysis methodology was utilized and data was gathered from sources in the public domain. Findings reveal industry’s contextual variables influence innovation and firm creation in the emerging biotechnology industry. Some of the emergent strategies for companies in this industry are establishing a family of firms, collaborating with business partners, locating their operation close to resources, and internationalizing their operation. These strategies, in turn, are influenced by the age and size of the companies. These findings can be explained by three major theories of competition; the influence of the external environment can be explained via the industrial organization perspective, while the resources and innovative conduct, being of strategic imperatives can be described through the resource-based and the Schumpeterian views. These insights offer entrepreneur-managers and policy makers directions toward enhancing the process of innovation and firm development, which in turn can support the development of technology-intensive companies and industries.